Vision in the Space Environment - Hart, L.G (Canadian Journal of Optometry, 2021)
It must be noted that the subject discussed in this paper is not only one that is complex, but also one that is constantly changing. By the time a paper about the space environment reaches print, many of the ideas could well be obsolete. This article was planned with the practising optometrist in mind. To compliment an extensive literature which already exists on the subject, only the ideas that it was felt would be of interest to, and act as primer on the subject for the interested practitioner are introduced here.